A Case of Cyperus spp. and Imperata cylindrica Occurrences on Acrisol of the Dahomey Gap in South Benin as Affected by Soil Characteristics: A Strategy for Soil and Weed Management - Brahima Kone; Guillaume Lucien Amadji; Amadou Toure; Abou Togola; Mariame Mariko; Joël Huat (Applied and Environmental Soil Science)
Because of the limiting efficacy of common weed control methods on Cyperus spp. and Imperata cylindrica their occurrences in tropical agroecologies and the effect of soil properties in suppressing these species were investigated in south Benin (Cotonou), a typical ecology of the Dahomey gap. Weeds and soil samples were collected twice early and later in the rainy season in 2009 at four topographic positions (summit, upper slope, middle slope, and foot slope). Sampling was done according to Braun-Blanquet abundance indices (3 and 5) and the absence (0) of Cyperus and Imperata in a quadrat, respectively. The relationship between their respective abundances and soil parameters (texture, C, N, P, K, Na, Ca, Mg, and Fe) was explored. Weed occurrence was less related to soil texture, and Imperata growth was more influenced by soil nutrients (K, Ca, and Fe) than Cyperus spp. Soil cation ratios of K : Mg and Ca : Mg were the main factors that could be changed by applying K and/or Mg fertilizers to reduce Cyperus and/or Imperata occurrence. Maintaining high Fe concentration in soil at hillside positions can also reduce Imperata abundance, especially in the Dahomey gap.